2018
DOI: 10.12688/f1000research.14634.1
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and epigenetics of pediatric leukemia in the era of precision medicine

Abstract: Pediatric leukemia represents a heterogeneous group of diseases characterized by germline and somatic mutations that manifest within the context of disturbances in the epigenetic machinery and genetic regulation. Advances in genomic medicine have allowed finer resolution of genetic and epigenetic strategies that can be effectively used to risk-stratify patients and identify novel targets for therapy. This review discusses the genetic and epigenetic mechanisms of leukemogenesis, particularly as it relates to ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 85 publications
1
3
0
Order By: Relevance
“…Splenomegaly and hepatomegaly happen due to the absorption of platelets and lymphocytes in the spleen and liver because of white blood cells. Typically, the spleen reacts by taking it out from the blood (DeRenzo et al, 2018) (Ramos et al, 2018). Along with the research by DeRenzo and Ramos et al, this patient also had splenomegaly, which is visibly enlarged (± 12.76 cm) by the ultrasound.…”
Section: Resultssupporting
confidence: 53%
“…Splenomegaly and hepatomegaly happen due to the absorption of platelets and lymphocytes in the spleen and liver because of white blood cells. Typically, the spleen reacts by taking it out from the blood (DeRenzo et al, 2018) (Ramos et al, 2018). Along with the research by DeRenzo and Ramos et al, this patient also had splenomegaly, which is visibly enlarged (± 12.76 cm) by the ultrasound.…”
Section: Resultssupporting
confidence: 53%
“…In recent years, a large number of studies have shown that the cause of leukemia is not only limited to chromosome abnormalities and gene mutations but also closely related to epigenetic and miRNA expression changes [30]. miRNAs not only inhibit the expression of target genes at the posttranscriptional level but also its expression is regulated by epigenetic mechanisms and acts directly or indirectly on key epigenetic enzymes such as DNA methyltransferase (DNMTs) [31].…”
Section: Discussionmentioning
confidence: 99%
“…The majority are under 18, with the peak age between two and ten years [ 81 , 82 , 83 ]. Pathophysiologically, ALL results from DNA damage causing the uncontrolled growth of lymphoid cells [ 84 , 85 , 86 ].…”
Section: Mscs In Allmentioning
confidence: 99%